Lung ultrasound to guide the administration of exogenous pulmonary surfactant in respiratory distress syndrome of newborn infants: A retrospective investigation study - Liu, Jing; Fu, Wei; Qin, Shen-Juan (Frontiers in Pediatrics, 2022)
Background:Lung ultrasound (LUS) has been successfully used in the diagnosis of respiratory distress syndrome (RDS),but its value in guiding the application of PS is still unclear.This paper explored whether the application of PS under LUS monitoring has some advantages,including (1) decreasing the misdiagnosis rate of RDS and decreasing probability of using PS;(2) reducing the dose of PS without reducing the therapeutic effect. Methods:This study included 2 parts.Part 1:To decide whether the LUS is good to differentiate RDS from other lung diseases in the premature infants.All patients who were diagnosed with RDS and required PS treatment based on conventional criteria were routinely examined by LUS.Then, according to LUS findings,we decided whether they needed to receive PS treatment. Part 2:To see the dose reduction of surfactant is applicable.In RDS patients diagnosed based on LUS presentation and treated with Curosurf,the dose of Curosurf was compared with that recommended by the European RDS management guidelines. Results:(1) Since March 2017,385 newborn infants admitted to our neonatal intensive care unit (NICU) met the traditional diagnostic criteria of RDS.Of these,only 269 cases were diagnosed with RDS and needed to accept PS treatment according to LUS manifestations.The other 116 infants who did not meet the criteria for ultrasound diagnosis of RDS did not receive PS supplementation but obtained a good outcomes, that is LUS findings decreased a misdiagnosis rate of RDS by 30.1% and subsequently resulted in a 30.1% reduction in PS use.(2) Among the 269 RDS patients diagnosed based on LUS findings,148 were treated with Curosurf (another 121 RDS infants who received domestic PS treatment were not included in the study group), and the average dose was 105.4 ± 24.3 mg/kg per time,which is significantly lower than the dose of 200 mg/kg per time recommended by the European RDS guidelines.(3)The mortality rate of RDS patients was 0%, and no patients complicated with ventilator-associated pneumonia or bronchopulmonary dysplasia in this study. Conclusion:LUS can decrease the misdiagnosis rate of RDS,thereby decreasing the probability of using PS and decreasing the dose of PS,and can help RDS infants to achieve better outcomes.